The Effect of Experiential Learning Model Integrated with Teachmint Media on Learning Motivation and Student Learning Outcomes in History Subjects - Pratiwi, Sabtiya; Sumardi, Sumardi; Umamah, Nurul; Marjono, Marjono (JURNAL HISTORICA, 2024)
This research aims to verify the application of the Experiential Learning learning model integrated with Teachmint media on student motivation and learning outcomes in history subjects. This research is quantitative research, with a One-Group Pretest-Posttest Design. One-Group Pretest-Posttest Design is research that uses one experimental class and includes pretest measurements, then treatment is given in the form of an experiential learning model integrated with Teachmint media, and measured again through a Posttest. This research only uses one experimental class without a comparison group/ control. The research population is students from classes X-A to X-K in the odd semester of the 2023/2024 academic year. The research technique used is the simple random sampling technique. Data collection through questionnaires, tests and documentation. Data analysis used a paired sample t test assisted by SPSS 25 for Windows software. The research results show that the application of the Experiential Learning model integrated with Teachmint media has a positive effect on motivation and learning outcomes. This can be explained by the ability of the experiential learning model which is able to foster enthusiasm and enthusiasm for learning, create a conducive learning environment and bring enjoyment. Students are actively involved, gain direct experience, and stimulate the development of students' creative thinking. The application of the Experiential Learning model integrated with Teachmint media in history learning activities can be beneficial for students because it can increase their motivation in learning history so that it also has a positive influence on their learning outcomes.